Toward Synergy and Collaboration to Expand the Supply of and Strengthen Primary Health Care in Nigeria’s Federal Context, with Special Reference to Ondo State - Atim, Chris; Bhatnagar, Aarushi (World Bank, Washington DC, 2013)
This study examines an innovative example of the expansion of supply and the strengthening of primary health care to improve key health-related Millennium Development Goal, or MDG indicators through synergy and collaboration between the federal Government of Nigeria (FGN) and state governments in an extreme federal context, and with particular reference to Ondo State. That is, the Nigerian Federal Constitution grants the federal government only very limited and indirect influence or control over the fiscal and financial affairs of state and local governments, such that 'plans, budgets, accounts and procurements are not subject to federal control and scrutiny'. Nor must the lower tiers account to the federal level for how funds transferred to them from the central level are used. The rest of case study is organized as follows. Section two describes the design of the HCP, including its interaction with the rest of the health system; section three discusses the targeting, identification, and enrolment system; section four examines the management of public funds within the HCP; section five analyses the management of the benefits package; section six reviews the information environment and monitoring systems of the HCP; section seven summarizes and analyses the evidence on the key theme of the study, which is the extent to which the HCP is expanding access to, and strengthening, primary health care within the federal system; and section eight looks at the pending agenda for action, drawing on the lessons learned and challenges for the HCP's future. The annexes present the country and health system context; a general overview of health system financing and delivery; a brief description of primary care and key supply-side efforts; and key data on Ondo State, including a description of the state's health system.